Priority Directions of the Regional Cooperation Model with Turkey and the Central Asian States (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Analysis of the thirty-year experience of this cooperation, which is based on the common cultural, linguistic, historical and religious unity of the independent states of Turkey and Central Asia, has become the center of attention of many researchers. The article examines the main features of the regional cooperation model between Turkey and the independent states of Central Asia and analyzes the ways of mutual cooperation.